1989
DOI: 10.1002/eji.1830190505
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of AIM, an activation inducer molecule of human lymphocytes, is dependent on the activation of protein kinase C

Abstract: AIM is an activation inducer molecule selectively expressed by activated lymphocytes through which agonistic proliferative signals can be triggered. The relationship between the expression of AIM with the activation of protein kinase C (PKC) has been studied. Different activators of PKC such as the active phorbol esters, phorbol myristate acetate and phorbol dibutyrate, or the phorbol-related ester mezerein were able to induce AIM expression on peripheral blood lymphocytes as assessed by immunofluorescence flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
(18 reference statements)
0
25
0
1
Order By: Relevance
“…PMA is capable of inducing CD69 expression via protein kinase C, effectively bypassing the TCR and thus Lck dependency. 23 PBMCs were placed into overnight culture with OKT3 in the presence or absence of dasatinib, and CD69 expression was analyzed by flow cytometry. As shown, CD69 is readily induced on OKT3-stimulated T cells but completely inhibited when dasatinib was added ( Figure 3A top panels).…”
Section: Dasatinib-mediated T-cell Inhibition Can Be Overcome By Stimmentioning
confidence: 99%
“…PMA is capable of inducing CD69 expression via protein kinase C, effectively bypassing the TCR and thus Lck dependency. 23 PBMCs were placed into overnight culture with OKT3 in the presence or absence of dasatinib, and CD69 expression was analyzed by flow cytometry. As shown, CD69 is readily induced on OKT3-stimulated T cells but completely inhibited when dasatinib was added ( Figure 3A top panels).…”
Section: Dasatinib-mediated T-cell Inhibition Can Be Overcome By Stimmentioning
confidence: 99%
“…The analysis of the requirements for CD69 expression in lymphoid cells has suggested that sustained PKC activation could be responsible for TcRICD3-mediated CD69 induction [3,14,15]. However, in NK cells IL-2 is likely to trigger [I 123811 Supported by grants from the CNR Progetto Bilaterale and the Associazione Italiana Ricerca sul Cancro.…”
Section: Introductionmentioning
confidence: 99%
“…We have also provided data indicating that regardless of the proliferative ability, the large miijority of BMT recipient Tcells were capable of dc novo expressing the C"D69 surface antigen, an event which takes place rapidly in T cells upon nctivation and is PKC-dcpcndent. thus reflecting the capacity of the cn/yme to induce gene expression [12]. However.…”
Section: Discussionmentioning
confidence: 99%
“…Firsl. we have assessed the capacity ofT cells lYom IIMT recipients to express the CD69 molecule, an curly aclivalion antigen dc novo synthesized after stimulation of PKC [12]. in addition, since anti-CD6y MoAbs can trigger agonistic signals complementary to PKC activation which activate lymphocyte proliferation [13].…”
mentioning
confidence: 99%